Inventory and Risk Analysis of Naturalized Exotic Species from the Cibodas Botanical Garden Collection Recorded in the Remnant Forest of Cibodas - Dwinda Mariska Putri; Dadang Sunandar; Dadang Suherman; Decky Indrawan Junaedi; Muhammad Efendi; Risha Amilia Pratiwi; Vandra Kurniawan (Jurnal Penelitian Hutan dan Konservasi Alam, 2022)
BBotanic Gardens cultivates exotic species for the purpose of ornamental plants. Moreover, these exotic species have the probability to escape the garden area and naturalized in adjacent forests. Cibodas Botanical Garden (CBG) is adjacent to four remnant forests: Jalan akar, Bengkel, Lumut, and Wornojiwo forests. There are several reports of naturalized CBG collections in Wornojiwo, thus this study does the inventory of naturalized exotic CBG collections in Cibodas remnant forests and perform Tropical Weed Risk Assessment Protocol (TWRAP) of these species. We found 26 CBG exotic species naturalized in remnant forests and more naturalized exotic species in Lumut and Jalan Akar forests than Wornojiwo and Bengkel forests. We presumed the topographic condition in Bengkel forest inhibit the spread of exotic species, meanwhile Jalan akar forest was located in the center area of CBG therefore holds the greatest number of naturalized exotic species. We found the domination of Chimonobambusa qudrangularis in Wornojiwo forest inhibiting other exotic species growth. The largest figure of the naturalized species belong to the family of Asteraceae, followed by Solanaceae, Marantaceae, Fabaceae, and Acanthaceae. The TWRAP assessment score results of the 81% naturalized species were above 10. Therefore TWRAP can be used as an early screening for botanic gardens exotic species naturalization probability. CBG commits to support the post-2020 biodiversity CBD target, with this inventory CBG can monitor the spread of CBG exotic plant collections that threaten native plant diversity and prevent future spreading of other exotic species.